Poverty and musculoskeletal impairment in Rwanda. - Rischewski, D; Kuper, H; Atijosan, O; Simms, V; Jofret-Bonet, M; Foster, A; Lavy, C (2008)
The recently adopted UN Convention on the Rights of Persons with Disabilities acknowledges the need to address social exclusion and poverty of persons with disabilities. However, policy makers, especially in low-income countries, often lack information about the socioeconomic situation of this vulnerable group of society. This study aimed to assess the association between poverty and musculoskeletal impairment (MSI) in Rwanda. A nationwide population-based matched case-control study was undertaken in Rwanda. Data were collected on education, literacy, employment, household expenditure and assets for 345 cases and 532 matched controls. Conditional logistic regression was performed, and the results indicated that adults with MSI in Rwanda are more likely to have no employment (odds ratio (OR)=3.3, 95% CI 2.1-5.2) while children with MSI are less likely to attend school (OR=0.4, 95% CI 0.2-0.9). Cases with MSI are disadvantaged vis-à-vis housing conditions and household size, potentially indicating crowding. However, cases with MSI were not poorer than controls in terms of assets or expenditure. These data suggest that increased efforts should be undertaken in Rwanda in order to ensure that children with disabilities are included in schools and that adults with disabilities can find appropriate employment opportunities.